Etiological factors of deafness and results of aided audiogram among below 12 years deaf children in a deaf school (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Deafness is the invisible disability and the commonest human sensory defects.  It leads to difficult speech development, poor educational and employment prospects of  chilhood. Comprehensive otologic and audiological evaluations are very much essential for  etiological assessment of hearing impaired children and management efficacy.Methods: A cross-sectional study was carried out with the aim to evaluate the etiological  factors, degree of hearing loss, type of hearing loss, and results of aided audiogram among  the below 12 years deaf children. The study included 100 deaf children below 12 years with  history of deafness and non-development of speech.Result: The etiology of deaf Children was diverse. Infection was the predominating etiological  factor (38%). The infections were: measles (31.5%), pneumonia (26.2%), typhoid (21.5%),  maternal rubella (5.2%), varicella (5.2%), mumps (5.2%) and meningitis (5.2%). 48% of deaf  child had a parental suspicion of deafness below the one year of age. 35% had a positive  family history and 32% had history of consanguinal marriage. The deaf children were managed  with hearing device, among them 89% with hearing aid and 11% with cochlear implant 42.7% of child used hearing aid in both ears. The results of aided audiogram reflected that, the gain  after using hearing aid within 31-60 dB were 80%. 10% in right ear, 71.10% in left year and  70.00% in both ears, so average gain after using hearing aid was 74% within 31- 60 dB. DOI:http://dx.doi.org/10.3329/bjo.v18i2.11981 Bangladesh J Otorhinolaryngol 2012; 18(2): 103-108